A hollow fiber composite membrane based on PVDF and preparation method thereof
By using surface-modified PVDF hollow fiber composite membrane and specific catalyst blending technology in the membrane catalytic oxidation system, the problems of membrane material selection and catalyst immobilization are solved, and efficient pollution removal and long-term stability are achieved.
Patent Information
- Application Number
- CN202411864681.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-08
AI Technical Summary
Existing membrane catalytic oxidation systems have challenges in membrane material selection and catalyst immobilization, resulting in a decrease in membrane flux and a decrease in separation efficiency, making catalyst loss difficult to reuse.
The hollow fiber composite membrane with PVDF as the substrate is used to improve hydrophilicity through surface modification and reduce pollution adsorption; specific catalysts are blended to ensure stable fixation and efficient utilization of the catalyst, and the pore structure is optimized to maintain high membrane flux and separation efficiency.
It achieves excellent pollution resistance, improves the efficiency of the catalyst and the overall performance of the membrane, extends the service life of the membrane, and reduces operating costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultrafiltration membranes, and in particular to a hollow fiber composite membrane using PVDF as a substrate and a preparation method thereof. Background Art
[0002] With the acceleration of industrialization, environmental pollution, especially water pollution and waste gas pollution, has become a severe challenge facing the world. Traditional water treatment and waste gas purification technologies have been unable to meet the increasingly stringent environmental protection requirements due to their low efficiency, high energy consumption, and complex operation. In this context, membrane separation technology has gradually become one of the important methods in the field of water treatment and waste gas treatment with its advantages of high efficiency, energy saving, and easy operation.
[0003] In order to solve the above problems, researchers have proposed membrane catalytic oxidation technology, which combines membrane separation technology with catalytic oxidation reaction, improves reaction efficiency through membrane separation, and uses catalysts to promote the oxidation and degradation of pollutants. This technology can not only increase the reaction rate, but also effectively prevent the loss of catalysts, thereby improving the long-term stability of the system. However, the existing membrane catalytic oxidation system still faces many challenges in practical applications, especially in the selection of membrane materials and the immobilization of catalysts.
[0004] As a high-performance membrane material, polyvinylidene fluoride (PVDF) has been widely used in the field of membrane separation due to its good chemical stability, mechanical strength and heat resistance. However, when PVDF membranes are used in catalytic oxidation processes, their limitations are fully exposed. When treating complex wastewater and waste gas, PVDF membranes are easily contaminated by organic matter, bacteria and oxidation products, resulting in a rapid decrease in membrane flux and a significant reduction in separation efficiency. This not only seriously affects the treatment effect of membrane separation technology, but also shortens the service life of the membrane and increases operating costs.
[0005] The problem of catalyst immobilization is also one of the key factors restricting the development of membrane catalytic oxidation technology. Traditional catalysts mostly exist in a free state and are easily lost during the reaction process, making it difficult to reuse the catalyst, reducing the processing efficiency and increasing the processing cost. Therefore, how to effectively fix the catalyst and improve the utilization efficiency of the catalyst and the overall performance of the membrane has become an important direction for the further development of membrane catalytic oxidation technology.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide a hollow fiber composite membrane with PVDF as the substrate, which improves hydrophilicity and reduces pollution adsorption through surface modification to achieve excellent anti-pollution performance; adopts specific catalyst blending to ensure stable fixation and efficient utilization of the catalyst; and optimizes the pore structure to maintain high membrane flux and separation efficiency without being affected by pollution.
[0008] The second purpose of the present invention is to provide a method for preparing the above-mentioned hollow fiber composite membrane based on PVDF. The preparation method is simple to operate and overcomes the problems of poor anti-pollution property of PVDF membrane, unstable catalyst immobilization and decreased membrane flux in the prior art.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are specially adopted: A hollow fiber composite membrane with PVDF as a substrate is mainly made of the following raw materials, measured by weight: 10-14 parts of polyvinylidene fluoride, 1-4 parts of polyvinyl pyrrolidone, 10-15 parts of additives, 60-80 parts of solvents and 0.5-3 parts of catalysts.
[0010] Preferably, as a further feasible embodiment, in parts by mass: 11-13 parts of polyvinylidene fluoride, 2-3.5 parts of polyvinyl pyrrolidone, 11-13 parts of additives, 65-75 parts of solvents, and 1-2.5 parts of catalysts.
[0011] Preferably, as a further feasible embodiment, in parts by mass: 12 parts of polyvinylidene fluoride, 3 parts of polyvinyl pyrrolidone, 12 parts of additives, 70 parts of solvents, and 2 parts of catalysts.
[0012] Preferably, the raw material also includes a soluble additive, the content of which is 5-10% of the polyvinylidene fluoride.
[0013] Preferably, the catalyst is one or more of graphene oxide and titanium dioxide.
[0014] The raw materials used in the present invention are polyvinylidene fluoride (PVDF) as the base membrane material, which provides the main structure and strength for the composite membrane of the present invention; polyvinylidene fluoride itself is a hydrophobic material, but the present invention reduces the attachment of pollutants and the clogging of the membrane by adding polyvinyl pyrrolidone and using surface modification technology, and significantly improves the filtration performance and anti-fouling performance of the hollow fiber composite membrane of the present invention; polyethylene glycol is used as a soluble additive to further improve the hydrophilicity and anti-fouling properties of the membrane and extend the service life of the membrane; the additive ethanol and the solvent dimethylacetamide jointly regulate the viscosity and fluidity of the membrane liquid to ensure the uniformity and stability of the membrane liquid. Graphene oxide and titanium dioxide are used as catalysts to promote the catalytic oxidation reaction and improve the catalytic performance of the membrane; graphene oxide and titanium dioxide have different catalytic mechanisms and active sites, and act together in the membrane to form a multi-level catalytic system; under the irradiation of ultraviolet light, titanium dioxide exhibits a stronger photocatalytic activity combined with the reduction and oxidation properties of graphene oxide, which significantly improves the catalytic oxidation efficiency of the membrane.
[0015] The present invention also provides a method for preparing the hollow fiber composite membrane using PVDF as a substrate, comprising: preparing a casting solution; The prepared casting solution is passed through a spinning head to form continuous fibrous membrane filaments, and the membrane filaments are immediately immersed in a coagulation bath, so that the membrane filaments can be completely solidified through the exchange of solvents; The surface of the solidified membrane fibers is treated by gas phase plasma treatment, ultraviolet light irradiation or chemical modification to finally form a hollow fiber composite membrane with PVDF as the base material.
[0016] Preferably, the preparation method of the casting solution is as follows: Dimethylacetamide is added to a reaction vessel, followed by ethanol to form a solution; Adding polyvinylidene fluoride and polyvinyl pyrrolidone into the solution in a predetermined mass ratio and fully dissolving them; Adding additives and catalysts to the fully dissolved solution and stirring them to uniformly mix with the solution to form a membrane liquid; The viscosity of the membrane liquid is adjusted according to the requirements of the membrane to finally form the casting membrane liquid.
[0017] Preferably, the temperature of the coagulation bath is controlled at 20-30°C.
[0018] Preferably, the dissolution temperature of the polyvinylidene fluoride and polyvinyl pyrrolidone in the casting solution is 50-70°C.
[0019] Preferably, the catalyst is stirred for 10-30 min to ensure that the catalyst is evenly dispersed in the solution.
[0020] It can be seen from the above-mentioned preparation method of the composite membrane of the present invention that the preparation of the casting solution is one of the key steps in preparing the PVDF-based hollow fiber composite membrane. The synergistic effect between the components makes the composite membrane have an optimized pore structure and pore size distribution, which can maintain a high reaction flux and separation performance; the introduction of catalysts and surface modification significantly improves the anti-pollution performance of the composite membrane of the present invention, reduces the occurrence of membrane pollution and the attenuation of membrane flux; the use of ethanol can adjust the volatilization rate of the solvent and the viscosity of the membrane solution, and provide suitable fluidity and formability for the subsequent preparation of the membrane solution and the spinning process; the uniform dispersion of the catalyst can ensure the high efficiency of the membrane in the catalytic oxidation reaction, and the addition of additives can further improve the hydrophilicity and anti-pollution of the membrane; the appropriate viscosity can ensure the stability and continuity of the membrane solution during the spinning process, so as to prepare a uniform quality membrane filament.
[0021] Phase inversion at an appropriate temperature can ensure the stability and uniformity of the membrane fibers. At the same time, the temperature control of the coagulation bath also helps to adjust the pore size and pore structure of the membrane, thereby affecting the separation performance and catalytic efficiency of the membrane.
[0022] The surface of the membrane filaments after surface treatment will more easily form hydrogen bonds with water molecules, thereby enhancing the anti-pollution performance of the membrane and improving the ability of the membrane surface to repel pollutants; this helps to extend the service life of the membrane and reduce maintenance costs in practical applications. The preparation method of the present invention has simple steps and is easy to operate.
[0023] Compared with the prior art, the present invention has the following beneficial effects: The raw materials used in the present invention are polyvinylidene fluoride (PVDF) as the base membrane material, and the catalyst is mixed with the solution during the membrane preparation process so that the catalyst is evenly distributed inside and on the surface of the membrane material. The catalyst is added to the solution mainly composed of polyvinylidene fluoride by a blending method, and a hollow fiber membrane is prepared by a phase inversion method. In order to improve the hydrophilicity and anti-pollution properties of the composite membrane of the present invention, the present invention is chemically or physically modified.
[0024] The present invention blends the catalyst with the solution so that the catalyst can be evenly dispersed in the structure of the membrane to avoid the loss of the catalyst, and fixes the catalyst by phase conversion method to improve the catalytic reaction efficiency and long-term stability of the present invention. The hollow fiber structure adopted by the composite membrane of the present invention is because such a structure can provide a large specific surface area, can promote the catalytic reaction, and can also maintain a high flux and separation efficiency.
[0025] The hollow fiber composite membrane with PVDF as the substrate of the present invention is particularly suitable for catalytic oxidation treatment of complex pollutants containing organic pollutants, heavy metal ions, microorganisms, etc. The composite membrane can be regenerated by conventional backwashing or chemical cleaning means to extend the service life and ensure the stability of the membrane during long-term use. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] Example 1 The specific preparation process of the hollow fiber composite membrane with PVDF as the substrate in this embodiment is carried out according to the following steps: (1) First, prepare the casting solution by adding 10 g of polyvinylidene fluoride and 2 g of polyvinyl pyrrolidone into 60 mL of dimethylacetamide solution, and stir at 50 °C for 2 h using a magnetic stirrer until the solution is completely dissolved to form a uniform solution; (2) Add 1 g of polyethylene glycol to the solution and continue stirring for 20 min until it is completely dissolved; (3) Then, 0.5 g of graphene oxide and 2 g of titanium dioxide were added to the solution, and an ultrasonic treatment device was used to control the power to 500 W and the frequency to 40 kHz for 20 min to ensure that the graphene oxide and titanium dioxide particles were evenly dispersed in the solution; (4) After ultrasonic treatment, slowly add ethanol dropwise while stirring. A total of 10 mL of ethanol is added to make the solution reach a moderate viscosity to obtain a membrane solution suitable for wet spinning. (5) Pour the prepared membrane solution into the spinning device, set the spinning solution flow rate to 10 ml / min, the stretching ratio to 4 times, extrude the membrane solution through the spinning head to form continuous fibrous membrane filaments, and control the temperature of the entire spinning process at 25 °C to ensure the stability of the spinning process; (6) The spun membrane fibers are immediately immersed in a 30°C water coagulation bath for phase inversion. The phase inversion process lasts for about 5 minutes. During this period, the state of the membrane fibers is observed to ensure that the membrane surface begins to solidify so that the prepared membrane forms a hollow fiber structure. (7) taking the hollow fiber composite membrane out of the coagulation bath and washing it with deionized water to remove the solvent and unreacted residues; (8) Place the cleaned hollow fiber composite membrane in an oven, set the temperature to 50°C, and dry it for 24 hours to ensure that the membrane is completely dry. (9) Plasma equipment was used with a power of 60 W for 2 min to improve the hydrophilicity of the hollow fiber composite membrane and obtain a hollow fiber composite membrane with strong anti-pollution ability.
[0028] Example 2 The specific preparation process of the hollow fiber composite membrane with PVDF as the substrate in this embodiment is carried out according to the following steps: (1) First, prepare the casting solution by adding 12 g of polyvinylidene fluoride and 3 g of polyvinyl pyrrolidone into 70 mL of dimethylacetamide solution, and stir at 50 °C for 2 h using a magnetic stirrer until the solution is completely dissolved to form a uniform solution; (2) Add 1.5 g of polyethylene glycol to the solution and continue stirring for 30 min until it is completely dissolved; (3) Then, 1 g of graphene oxide and 1 g of titanium dioxide were added to the solution, and an ultrasonic treatment device was used to control the power to 500 W and the frequency to 40 kHz for 30 min to ensure that the graphene oxide and titanium dioxide particles were evenly dispersed in the solution; (4) After ultrasonic treatment, slowly add ethanol dropwise while stirring. A total of 12 mL of ethanol is added to make the solution reach a moderate viscosity to obtain a membrane solution suitable for wet spinning. (5) Pour the prepared membrane solution into the spinning device, set the spinning solution flow rate to 12 ml / min, the stretching ratio to 4.5 times, extrude the membrane solution through the spinning head to form continuous fibrous membrane filaments, and control the temperature of the entire spinning process at 25 °C to ensure the stability of the spinning process; (6) The spun membrane fibers were immediately immersed in a 30°C water coagulation bath for phase inversion. The phase inversion process lasted for about 4 minutes. During this period, the state of the membrane fibers was observed to ensure that the membrane surface began to solidify, so that the prepared membrane formed a hollow fiber structure. (7) taking the hollow fiber composite membrane out of the coagulation bath and washing it with deionized water to remove the solvent and unreacted residues; (8) Place the cleaned hollow fiber composite membrane in an oven, set the temperature to 50°C, and dry it for 24 hours to ensure that the membrane is completely dry. (9) Plasma equipment was used with a power of 60 W for 2 min to improve the hydrophilicity of the hollow fiber composite membrane and obtain a hollow fiber composite membrane with strong anti-pollution ability.
[0029] Example 3 The specific preparation process of the hollow fiber composite membrane with PVDF as the substrate in this embodiment is carried out according to the following steps: (1) First, prepare the casting solution by adding 14 g of polyvinylidene fluoride and 4 g of polyvinyl pyrrolidone into 80 mL of dimethylacetamide solution, and stir at 70 °C for 2 h using a magnetic stirrer until the solution is completely dissolved to form a uniform solution; (2) Add 1.4 g of polyethylene glycol to the solution and continue stirring for 30 min until it is completely dissolved; (3) Then, 1.5 g of graphene oxide and 1.5 g of titanium dioxide were added to the solution, and an ultrasonic treatment device was used to control the power to 500 W and the frequency to 40 kHz for 30 min to ensure that the graphene oxide and titanium dioxide particles were evenly dispersed in the solution; (4) After ultrasonic treatment, slowly add ethanol dropwise while stirring. A total of 11 mL of ethanol is added to make the solution reach a moderate viscosity to obtain a membrane solution suitable for wet spinning. (5) Pour the prepared membrane solution into the spinning device, set the spinning solution flow rate to 11 ml / min, the stretching ratio to 4 times, extrude the membrane solution through the spinning head to form continuous fibrous membrane filaments, and control the temperature of the entire spinning process at 25 °C to ensure the stability of the spinning process; (6) The spun membrane fibers were immediately immersed in a 20°C water coagulation bath for phase inversion. The phase inversion process lasted for about 4 minutes. During this period, the state of the membrane fibers was observed to ensure that the membrane surface began to solidify, so that the prepared membrane formed a hollow fiber structure. (7) taking the hollow fiber composite membrane out of the coagulation bath and washing it with deionized water to remove the solvent and unreacted residues; (8) Place the cleaned hollow fiber composite membrane in an oven, set the temperature to 55°C, and dry for 24 hours to ensure that the membrane is completely dry. (9) Plasma equipment was used with a power of 60 W for 2 min to improve the hydrophilicity of the hollow fiber composite membrane and obtain a hollow fiber composite membrane with strong anti-pollution ability.
[0030] Example 4 The specific preparation process of the hollow fiber composite membrane with PVDF as the substrate in this embodiment is carried out according to the following steps: (1) First, prepare the casting solution by adding 13 g of polyvinylidene fluoride and 3.5 g of polyvinyl pyrrolidone into 65 mL of dimethylacetamide solution, and stir at 60 °C for 2 h using a magnetic stirrer until the solution is completely dissolved to form a uniform solution; (2) Add 1 g of polyethylene glycol to the solution and continue stirring for 30 min until it is completely dissolved; (3) Then, 1 g of graphene oxide and 1 g of titanium dioxide were added to the solution, and an ultrasonic treatment device was used to control the power to 500 W and the frequency to 40 kHz for 30 min to ensure that the graphene oxide and titanium dioxide particles were evenly dispersed in the solution; (4) After ultrasonic treatment, slowly add ethanol dropwise while stirring. A total of 13 mL of ethanol is added to make the solution reach a moderate viscosity to obtain a membrane solution suitable for wet spinning. (5) Pour the prepared membrane solution into the spinning device, set the spinning solution flow rate to 12 ml / min, the stretching ratio to 4.5 times, extrude the membrane solution through the spinning head to form continuous fibrous membrane filaments, and control the temperature of the entire spinning process at 25 °C to ensure the stability of the spinning process; (6) The spun membrane fibers were immediately immersed in a 25°C water coagulation bath for phase inversion. The phase inversion process lasted for about 6 minutes. During this period, the state of the membrane fibers was observed to ensure that the membrane surface began to solidify, so that the prepared membrane formed a hollow fiber structure. (7) taking the hollow fiber composite membrane out of the coagulation bath and washing it with deionized water to remove the solvent and unreacted residues; (8) Place the cleaned hollow fiber composite membrane in an oven, set the temperature to 60°C, and dry for 24 hours to ensure that the membrane is completely dry. (9) Plasma equipment was used with a power of 60 W for 2 min to improve the hydrophilicity of the hollow fiber composite membrane and obtain a hollow fiber composite membrane with strong anti-pollution ability.
[0031] Example 5 The specific preparation process of the hollow fiber composite membrane with PVDF as the substrate in this embodiment is carried out according to the following steps: (1) First, prepare the casting solution by adding 11 g of polyvinylidene fluoride and 1 g of polyvinyl pyrrolidone into 75 mL of dimethylacetamide solution, and stir at 65 °C for 2 h using a magnetic stirrer until the solution is completely dissolved to form a uniform solution; (2) Add 1 g of polyethylene glycol to the solution and continue stirring for 30 min until it is completely dissolved; (3) Then, 0.5 g of graphene oxide and 0.5 g of titanium dioxide were added to the solution, and an ultrasonic treatment device was used to control the power to 500 W and the frequency to 40 kHz for 30 min to ensure that the graphene oxide and titanium dioxide particles were evenly dispersed in the solution; (4) After ultrasonic treatment, slowly add ethanol dropwise while stirring. A total of 15 mL of ethanol is added to make the solution reach a moderate viscosity to obtain a membrane solution suitable for wet spinning. (5) Pour the prepared membrane solution into the spinning device, set the spinning solution flow rate to 10 ml / min, the stretching ratio to 4 times, extrude the membrane solution through the spinning head to form continuous fibrous membrane filaments, and control the temperature of the entire spinning process at 25 °C to ensure the stability of the spinning process; (6) The spun membrane fibers were immediately immersed in a 30°C water coagulation bath for phase inversion. The phase inversion process lasted for about 4 minutes. During this period, the state of the membrane fibers was observed to ensure that the membrane surface began to solidify, so that the prepared membrane formed a hollow fiber structure. (7) taking the hollow fiber composite membrane out of the coagulation bath and washing it with deionized water to remove the solvent and unreacted residues; (8) Place the cleaned hollow fiber composite membrane in an oven, set the temperature to 50°C, and dry it for 24 hours to ensure that the membrane is completely dry. (9) Plasma equipment was used with a power of 60 W for 2 min to improve the hydrophilicity of the hollow fiber composite membrane and obtain a hollow fiber composite membrane with strong anti-pollution ability.
[0032] Comparative Example 1 The specific operation steps are the same as those in Example 2, except that the mass fraction of polyvinyl pyrrolidone is changed to 9 parts.
[0033] Comparative Example 2 The specific operation steps are the same as those in Example 2, except that the mass fraction of the additive is changed to 3 parts.
[0034] Comparative Example 3 The specific operation steps are the same as those in Example 2, except that the mass fraction of the catalyst is changed to 10 parts.
[0035] Example 1 The hollow fiber composite membranes with PVDF as the substrate prepared in the above examples and comparative examples were tested for performance. The prepared hollow fiber composite membranes were cut into equal parts for the following tests. The specific results are shown in Table 1.
[0036] Pore size and flux testing: Use a water contact angle meter to test the contact angle of the membrane; Use a conventional permeation flux test method to test the permeation flux of the membrane prepared by the above method at a pressure difference of 1 bar; Membrane anti-fouling test: The membrane anti-fouling test was carried out in simulated organic polluted water (solution containing bovine serum albumin). After 10 hours of filtration, the flux attenuation of each membrane was tested.
[0037] Catalytic oxidation performance test: The prepared composite membrane was installed in the membrane module, and the wastewater containing organic pollutants (phenol) was treated by the membrane catalytic oxidation system. The system was irradiated with an ultraviolet light source (λ=365 nm). The reaction temperature was 25°C and the reaction time was 2 hours. After catalytic oxidation treatment, the degradation rate of phenol was tested. Test of long-term stability of membrane: simulate the catalytic oxidation process under actual working conditions, conduct long-term operation test on the membrane, and test the catalytic degradation rate of the membrane after 30 days of continuous operation.
[0038] Table 1. Experimental conclusions
[0039] Based on the above data, we can draw the following conclusions: From the above data, it can be seen that the contact angles of the composite films in the embodiments are generally low, indicating that the composite films of the present invention have good hydrophilicity, especially the contact angle of Example 2 is less than 35°, showing the best hydrophilicity; the contact angles of the composite films in the comparative examples are higher than those in the embodiments, indicating that their hydrophilicity is poor, which is due to the changes in the components added to the solution of the present invention beyond the optimal range of the present invention. From Examples 1-5, it can be seen that when the total amount of catalyst is relatively high, it helps to enhance the catalytic oxidation performance of the film, especially titanium dioxide as a photocatalyst, which shows a stronger degradation ability under the irradiation of ultraviolet light.
[0040] It is particularly found that polyvinyl pyrrolidone added to a solution based on polyvinylidene fluoride can significantly improve the hydrophilicity and permeation flux of the membrane, because the content of polyvinyl pyrrolidone is relatively less, the hydrophilicity of the membrane is better and the anti-pollution performance is stronger; however, with reference to Comparative Example 1, it can be seen that the excessive addition of polyvinyl pyrrolidone leads to excessive swelling of the membrane result, affecting the performance of the membrane, so it is necessary to control the ratio of polyvinyl pyrrolidone with other components in the present invention. It can also be seen that when a single component in the comparative example changes too much or too little, it will affect the optimal ratio range with other components of the present invention, destroying the use performance of the membrane of the present invention. It is also further proved that the synergistic effect of each component between the present invention, when the component is missing, will have a serious impact on the performance of the hollow fiber composite membrane based on PVDF of the present invention, and its performance will be greatly reduced and far lower than the embodiment.
[0041] It can also be seen in the embodiments of the present invention that by adjusting the ratio of each component within the optimal ratio range of the present invention, especially Example 2, the prepared membrane can have excellent catalytic performance, hydrophilicity, anti-pollution, high flux and long-term stability, and has a significant catalytic oxidation effect under ultraviolet light.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A hollow fiber composite membrane based on PVDF, characterized in that: The invention is mainly prepared from the following raw materials by weight: 10-14 parts of polyvinylidene fluoride, 1-4 parts of polyvinyl pyrrolidone, 10-15 parts of additives, 60-80 parts of solvents and 0.5-3 parts of catalysts.
2. The hollow fiber composite membrane based on PVDF according to claim 1, characterized in that: In parts by mass: 11-13 parts of polyvinylidene fluoride, 2-3.5 parts of polyvinyl pyrrolidone, 11-13 parts of additives, 65-75 parts of solvents, and 1-2.5 parts of catalysts.
3. The hollow fiber composite membrane based on PVDF according to claim 1, characterized in that: In parts by mass: 12 parts of polyvinylidene fluoride, 3 parts of polyvinyl pyrrolidone, 12 parts of additives, 70 parts of solvents, and 2 parts of catalysts.
4. The hollow fiber composite membrane with PVDF as the substrate according to any one of claims 1 to 3, characterized in that: The raw materials also include soluble additives, the content of which is 5-10% of the polyvinylidene fluoride.
5. The hollow fiber composite membrane with PVDF as the substrate according to any one of claims 1 to 3, characterized in that: The raw materials also include a catalyst which is one or more of graphene oxide and titanium dioxide.
6. A method for preparing a hollow fiber composite membrane with PVDF as a substrate as claimed in any one of claims 1 to 5, characterized in that: include: preparing a casting solution; The prepared casting solution is passed through a spinning head to form continuous fibrous membrane filaments, and the membrane filaments are immediately immersed in a coagulation bath, so that the membrane filaments can be completely solidified through the exchange of solvents; The surface of the solidified membrane fibers is treated by gas phase plasma treatment, ultraviolet light irradiation or chemical modification to finally form a hollow fiber composite membrane with PVDF as the base material.
7. The method for preparing a hollow fiber composite membrane based on PVDF according to claim 6, characterized in that: The preparation method of the casting solution is as follows: Dimethylacetamide is added to a reaction vessel, followed by ethanol to form a solution; Adding polyvinylidene fluoride and polyvinyl pyrrolidone into the solution in a predetermined mass ratio and fully dissolving them; Adding additives and catalysts to the fully dissolved solution and stirring them to uniformly mix with the solution to form a membrane liquid; The viscosity of the membrane liquid is adjusted according to the requirements of the membrane to finally form the casting membrane liquid.
8. The method for preparing a hollow fiber composite membrane based on PVDF according to claim 6, characterized in that: The temperature of the coagulation bath is controlled at 20-30°C.
9. The method for preparing a hollow fiber composite membrane based on PVDF according to claim 7, characterized in that: The dissolution temperature of the polyvinylidene fluoride and polyvinyl pyrrolidone in the casting solution is 50-70°C.
10. The method for preparing a hollow fiber composite membrane based on PVDF according to claim 7; characterized in that: The catalyst is stirred for 10-30 minutes to ensure that the catalyst is evenly dispersed in the solution.